ENHANCING CONCEPTUAL UNDERSTANDING IN FOUNDATIONAL PHYSICS: A MINI REVIEW OF GAMIFICATION’S ROLE IN LINEAR KINEMATICS - Abdul Rahim, Nur Syahida; Abu Bakar, Mohd Muzammir Firdaus; Saaid, Siti Irma Yuana Sheikh Mohd (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
This paper proposes an investigation into the effectiveness of an application-based and gamified approach for teaching the foundational concepts of Linear Kinematics to foundation-level students in physics. A systematic review of current literature confirms a strong and growing trend in the use of gamification in physics education to address common student issues of low motivation, perceived difficulty, and poor conceptual grasp. Research indicates that integrating game mechanisms significantly enhances student engagement, motivation, and academic performance by transforming physics from an abstract, theoretical subject into an appealing, interactive experience. Furthermore, the literature strongly supports the use of interactive simulations and application-based learning to make complex concepts, such as force and energy, tangible and easier to grasp through direct manipulation of variables and real-time observation of outcomes. Specifically targeting foundation or college-level students, gamification has been shown to improve problem-solving skills, critical thinking, and long-term retention of concepts. This mini review paper establishes a solid justification for the proposed application based gamified intervention, highlighting its potential to revolutionise the teaching of Linear Kinematics by fostering active learning and deeper conceptual understanding. The future study aims to empirically validate this approach’s impact on learning outcomes compared to traditional teaching methods.